2022
DOI: 10.1055/a-1534-2599
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Combined First Trimester Screening for Preeclampsia into Routine Ultrasound Examination

Abstract: Introduction The Fetal Medicine Foundation (FMF) London has developed a first trimester screening algorithm for preeclampsia (PE), based on maternal characteristics and past risk factors, mean arterial pressure (MAP), uterine artery pulsatility index (UtA-PI), and placental growth factor (PlGF). The aim of this study was to determine the feasibility of integrating PE screening into routine practice. Material and Methods All pregnancies with a fetal crown-rump length of 45 – 84 mm presenting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The value of PAPP-A in screening for PE has been extensively discussed; including PAPP-A into routine screening for pPE does not improve the performance of screening [12, 20, 21]. Screening for aneuploidies is offered to all pregnant women in Switzerland and there is a high acceptance for such screening [32]. PAPP-A is therefore often obtained for aneuploidy screening and routinely included into PE-screening.…”
Section: Discussionmentioning
confidence: 99%
“…The value of PAPP-A in screening for PE has been extensively discussed; including PAPP-A into routine screening for pPE does not improve the performance of screening [12, 20, 21]. Screening for aneuploidies is offered to all pregnant women in Switzerland and there is a high acceptance for such screening [32]. PAPP-A is therefore often obtained for aneuploidy screening and routinely included into PE-screening.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that uterine artery hemodynamic parameters in patients with preeclampsia are signifcantly higher than those in normal pregnant women [19]. Ultrasound technology enables the noninvasive and real-time assessment of hemodynamic parameters in vital organs of pregnant women and fetuses [20]. However, till date, the roles of serum SIRT1 and uterine hemodynamics in the progression of preeclampsia are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In Switzerland first trimester ultrasound screening as part of routine pregnancy care has a high uptake and acceptance 26 . As recently published, about 90% of women presenting for first trimester ultrasound decide to screen for fetal trisomies 26 . Switzerland was one of the first countries worldwide to implement cffDNA into routine screening in 2015 18 .…”
Section: Discussionmentioning
confidence: 99%